Heinrich Freiherr von Ohlendorff. Ein Hamburger Kaufmann im Spiegel der Tagebücher seiner Ehefrau Elisabeth - Schröder, Hans Joachim (Mäzene für Wissenschaft, 2014)
Heinrich von Ohlendorff became one of Hamburg's richest merchants by trading with Peru-Guano. Together with his wife Elisabeth he founded a family of twelve. In 1880, Elisabeth began to write her diary. Until her death she filled 45 obese notebooks with astonishing regularity. The approximately 20,000 pages provide exciting insights into the life of an up-and-coming family that is firmly integrated into the society of Hamburg's upper middle classes. The pages make it possible to portray Heinrich von Ohlendorff in the mirror of his wife's diaries. At the same time, it is possible to draw a fascinating panoramic picture of the "fine" Hamburg society at the beginning of the 20th century. This is the first biography of this merchant from Hamburg who was one of the donors of the Hamburg Scientific Foundation.Translated with www.DeepL.com/Translator